Analysis of the possibilities of Poland's participation in the utilization of hazardous chemicals based on the experience of the Danish RECLIB operation - Tomasz Binek; Krzysztof Pająk (Journal of Modern Science, 2018)
Objectives Analysis of the possibilities of Poland's participation in the utilization of hazardous chemicals based on the experience of the Danish RECLIB operation. The article reviews the implementation of the maritime policy by the Kingdom of Denmark as the examples of an operation, carried out in 2016, under the code name Reclib, whose the main aim was to remove harmful chemical substances from Libya.